Effects of pulse crop types and extrusion parameters on the physicochemical properties, in vitro and in vivo starch digestibility of pet foods. Issue 3 (20th January 2022) - Ren, Yikai; Quilliam, Chloe; Weber, Lynn P.; Warkentin, Thomas D.; Tulbek, Mehmet C.; Ai, Yongfeng
Abstract: Background and objectives: This study aimed to tackle the research gaps regarding how different pulse types and extrusion conditions influenced starch digestibility and quality attributes of extruded dry pet foods. Flours of round pea, lentil, faba bean, wrinkled pea, and rice (control) were selected to extrude dry pet foods under "mild" (C1) and "extreme" (C2) conditions. Physicochemical properties, in vitro and in vivo starch digestibility of the resulting pet foods were characterized. Findings: Under both conditions, wrinkled pea pet foods showed significantly lower damaged/gelatinized‐starch contents and less molecular breakdown than other samples. For all the formulations, the C2 condition gelatinized and degraded starch to greater extents than C1. Consistent with the structural and physicochemical properties of the extrudates, wrinkled pea pet foods exhibited notably lower digestibility in both in vitro and in vivo studies than other formulations. Conclusions: Both pulse types and extrusion parameters effectively impacted the quality and starch digestibility of the extruded pet foods. Wrinkled pea flours showed high amylose contents and could be a promising ingredient for producing pet foods rich in resistant starch. Significance and novelty: This study revealed the interrelationships among the structures, physicochemical properties, and starch digestibility of extruded pet foods formulated with normal and high‐amylose pulse flours.